Pengembangan Media Pembelajaran Komik pada Materi Teks Negosiasi Siswa Kelas X SMKS Pab 5 Klambir Lima (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This research is motivated by the low interest and skills of class X students of SMKS PAB 5 Klambir Lima which is caused by less interesting teaching methods and minimal innovation of learning media utilized during teaching and learning activities in the classroom. This study aims to develop comic learning media on negotiation text material for class X students. The research methodology uses research and development with the ADDIE model consisting of five stages, namely analysis, design, development, implementation, and evaluation. The population in the study were class X students of SMKS PAB 5 Klambir Lima with a sample size of 28 students. Data collection was carried out through observation, interviews, questionnaires, and documentation, then analyzed using a Likert scale, mean, and the N-Gain formula to obtain valid and accurate results. The results of the study indicate that the comics developed were declared very feasible by media experts 96%, language experts 96%, and material experts 92%. The level of practicality of the comics also obtained very practical results with teacher responses of 4.7 and students 3.30. In addition, the results of the effectiveness of comics show an increase in students' writing skills, with an average N-Gain of 81.35% in the effective category. This study shows that comics can be an alternative teaching material that supports the learning process and learning outcomes experience significant development.